2022
DOI: 10.1108/rpj-09-2021-0235
|View full text |Cite
|
Sign up to set email alerts
|

Study on the influence of process parameters on high performance Ti-6Al-4V parts in laser powder bed fusion

Abstract: Purpose The purpose of this paper is to improve the performance and quality of Ti-6Al-4V fabricated by laser powder bed fusion. Design/methodology/approach Single-track experiments were conducted during the fabrication process to obtain the single tracks with excellent wettability to narrow the process parameter window. The effects of process parameters on the build surface, cross-section, relative density, defects, surface roughness, microstructure and mechanical properties of the parts were analyzed throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…and they result in mechanical properties similar to conventional manufacturing technologies (Mercelis and Kruth, 2006; Caulfield, Mchugh and Lohfeld, 2007; S. Azar et al , 2021; Sadeghi and Mohseni, 2022; Wang et al , 2022; Mohseni et al , 2023).…”
Section: Introductionmentioning
confidence: 96%
“…and they result in mechanical properties similar to conventional manufacturing technologies (Mercelis and Kruth, 2006; Caulfield, Mchugh and Lohfeld, 2007; S. Azar et al , 2021; Sadeghi and Mohseni, 2022; Wang et al , 2022; Mohseni et al , 2023).…”
Section: Introductionmentioning
confidence: 96%
“…A superalloy is a kind of high-temperature resistant metal material composed of Ni, Co, and other elements. Due to its good oxidation resistance, corrosion resistance, and excellent strength at high temperatures, it is often used in equipment such as aero-engine and industrial gas turbines [2]. GH99, a typical aging strengthening nickel-base superalloy, is mainly used in high-temperature structural materials such as aerospace turbines and power station turbines.…”
Section: Introductionmentioning
confidence: 99%
“…Choy, Sing Ying, et al [ 12 ] produced strut-based and honeycomb lattice structures by L-PBF processing and found that abrupt shear failure took place at the opposite corners of the lattice samples during compression testing since the diagonal struts in the planar section were oriented parallel to the compression direction. Additionally, the authors in reference [ 13 ] employed an experimental approach to find the processing conditions that can fabricate high-performance Ti6Al4V parts using the L-PBF process.…”
Section: Introductionmentioning
confidence: 99%